2017
DOI: 10.1016/j.socscimed.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

What caused the 2012 dengue outbreak in Pucallpa, Peru? A socio-ecological autopsy

Abstract: Dengue is highly endemic in Peru, with increases in transmission particularly since vector re-infestation of the country in the 1980s. Pucallpa, the second largest city in the Peruvian Amazon, experienced a large outbreak in 2012 that caused more than 10,000 cases and 13 deaths. To date, there has been limited research on dengue in the Peruvian Amazon outside of Iquitos, and no published review or critical analysis of the 2012 Pucallpa dengue outbreak. This study describes the incidence, surveillance, and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Figure 2 shows seasonal trends in dengue cases. The 2012 dengue outbreak also occurred during the rainy season, as a result of proximal and distal causes discussed in Charette et al 26 The average age of patients with dengue in Pucallpa during the study period was 23.9 years old (95% CI: 23.5-24.1) and 52% of all cases were female patients. The mean average weekly temperature (lagged 4 weeks) was 25.2°C in the dry season compared with 26.2°C in the rainy season.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure 2 shows seasonal trends in dengue cases. The 2012 dengue outbreak also occurred during the rainy season, as a result of proximal and distal causes discussed in Charette et al 26 The average age of patients with dengue in Pucallpa during the study period was 23.9 years old (95% CI: 23.5-24.1) and 52% of all cases were female patients. The mean average weekly temperature (lagged 4 weeks) was 25.2°C in the dry season compared with 26.2°C in the rainy season.…”
Section: Resultsmentioning
confidence: 86%
“…25 The 2012 Pucallpa dengue outbreak highlights gaps in our understanding of how climatic and social determinants interact to drive disease epidemics. 26 With the increasing frequency of extreme weather events in the Peruvian Amazon, more research is needed on effective dengue prevention strategies based on an improved understanding of the interaction between social determinants, weather, and dengue incidence. 27,28 We address this gap in the literature by examining how meteorological exposures affected dengue incidence among different subpopulations-compared across different districts, genders, and ages-in Pucallpa, Peru, from 2004 to 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Our study identifies a peak of incidence in 2012, consistent with a study in Peru by Charette et al which describe a large outbreak of dengue in 2012 that caused more than 10,000 cases and 13 deaths in Ucayali, a region with borders to the East of the territory included in our study. It was suggested that the outbreak was triggered by the introduction of a new virus serotype (DENV-2 in Asia/America) [22]. Our observation indicates that this important outbreak was developed in the absence of the El Niño.…”
Section: Discussionmentioning
confidence: 59%
“…Our observation indicates that this important outbreak was developed in the absence of the El Niño. The introduction of a new serotype, increased frequency of travel, rapid urbanization and inadequate water management were determinant factors in the spread and transmission of the virus in that year [1, 22]. This suggests that in years when ENSO is absent there may be a high incidence of dengue virus infection, so the presence of this weather phenomenon alone would not be necessary or sufficient to produce an increase in the incidence of dengue in a determined endemic territory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation